2021
DOI: 10.3390/jcm10091881
|View full text |Cite
|
Sign up to set email alerts
|

Tinnitus and Neuropsychological Dysfunction in the Elderly: A Systematic Review on Possible Links

Abstract: Introduction: Tinnitus is a common and disabling symptom often associated with hearing loss. While clinical practice frequently shows that a certain degree of psychological discomfort often characterizes tinnitus suffers, it has been recently suggested in adults as a determining factor for cognitive decline affecting attention and memory domains. The aim of our systematic review was to provide evidence for a link between tinnitus, psychological distress, and cognitive dysfunction in older patients and to focus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…The findings indicated that individuals with tinnitus often faced concurrent conditions such as depression, poor sleep, and anxiety (Clarke et al, 2018 ). A recently published study has unveiled that elderly tinnitus patients face a considerably higher risk of dementia, and they also exhibit associations with other cognitive impairments, including anxiety, depression, and sleep difficulties (Malesci et al, 2021 ). However, contrary to expectations, an investigational study conducted in 2021 revealed a positive association between tinnitus and enhanced cognitive performance in non-Hispanic elderly individuals with hearing loss.…”
Section: Discussionmentioning
confidence: 99%
“…The findings indicated that individuals with tinnitus often faced concurrent conditions such as depression, poor sleep, and anxiety (Clarke et al, 2018 ). A recently published study has unveiled that elderly tinnitus patients face a considerably higher risk of dementia, and they also exhibit associations with other cognitive impairments, including anxiety, depression, and sleep difficulties (Malesci et al, 2021 ). However, contrary to expectations, an investigational study conducted in 2021 revealed a positive association between tinnitus and enhanced cognitive performance in non-Hispanic elderly individuals with hearing loss.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies assert an increased risk of psychiatric comorbidities among patients with tinnitus [ 48 ], but they also report mild psychiatric symptoms and a worsening of quality of life [ 49 , 50 ]. Recent literature argues there is a complex association among tinnitus perception, emotional disorders, and cognitive dysfunction, however the causal link is still not fully understood [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although it is largely demonstrated that psychiatric discomfort is present in a large number of tinnitus suffers [ 23 , 48 ], actual evidence does not allow us to establish, with certainty, if tinnitus matters as an independent risk factor for cognitive impairment or the evolution to dementia [ 49 ]. Nevertheless, a previous evaluation of glucose metabolic connectivity through FDG-PET has already shown a lower metabolism in the right superior temporal pole and in the fusiform gyrus among subjects with MCI and tinnitus, unlike those with only a cognitive impairment [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several cross-sectional studies have consistently demonstrated an association between cognitive decline and HL across different populations [ 9 ]. Indeed, HL appears to exacerbate cognitive deficits in the elderly and may serve as a prognostic factor for mild cognitive impairment (MCI) [ 10 ]. Moreover, prospective cohort studies have suggested that the use of hearing aids in patients with HL can reduce cognitive decline in older adults [ 9 ].…”
Section: Introductionmentioning
confidence: 99%